2014
DOI: 10.1074/jbc.m114.563981
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of a Gatekeeper Residue on the Aggregation of Transthyretin

Abstract: Background: Proteins have adopted negative design to diminish aggregation.Results: The replacement of Lys-35 by Leu increases the amyloidogenicity of the 26–57 segment of TTR as well as the entire protein.Conclusion: Lys-35 is as a gatekeeper residue in TTR, and its protective effect is suppressed by heparin.Significance: The elucidation of the principles that govern protein aggregation is helpful for the design of strategies against amyloid diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 70 publications
(89 reference statements)
2
32
3
Order By: Relevance
“…The quantity of information carried by the amino acid sequence is insufficient to unambiguously determine the conformation of each residue [58][59][60]. This work postulates that the aqueous environment remains an integral factor in the folding process and compensates for the observed shortfall in information [9,15,[58][59][60].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The quantity of information carried by the amino acid sequence is insufficient to unambiguously determine the conformation of each residue [58][59][60]. This work postulates that the aqueous environment remains an integral factor in the folding process and compensates for the observed shortfall in information [9,15,[58][59][60].…”
Section: Discussionmentioning
confidence: 95%
“…The same mechanism can be adopted for the analysis of mutation influence on the resultant stability of particular β-fragments of transthyrein [58].…”
Section: Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…In the presence of heparin, however, the fibril formation of the 44–65 peptide was greatly enhanced, especially in the W50R variant, indicating that the inhibitory effect of the W50R mutation can be offset in the presence of heparin. Previously, it was reported that the protective effect of Lys‐35 on the amyloidogenic aggregation of transthyretin is strongly suppressed by heparin, probably through neutralization of side chain positive charges . Thus, it is plausible that the addition of a positively charged amino acid (Arg‐50) into the second amyloidogenic segment strengthens interactions with heparin, canceling out the inhibitory effect of the mutation by neutralizing positive charges.…”
Section: Discussionmentioning
confidence: 99%
“…It has long been recognized that in the general case of protein aggregation, and of amyloid formation in particular, hydrophobic interactions play a key role in protein condensation. In this regard, TTR aggregation is no different . Furthermore, the importance of a yet unknown network of hydrogen bonding that may be formed across dimers may also be relevant.…”
Section: Discussionmentioning
confidence: 99%